Religious Building for the City Identity: The Case of Antioch - Diker, Melisa; Erkan, Nilgun Colpan (KARE PUBL, 2017)
The term of urban identity includes all physical, cultural, historical, economical, features that distinguish it from the other cities. Symbol buildings or landmarks, which are the ones of reflecting urban identity, play a significant role in remembarance and recognation of the city. Religious buildings in the city structures can be seen and noticed easily thanks to their locations, they differ from other structures through their shapes and sizes. These make religious buildings strong landmarks and easily remembered by both tourists and residents. In this study, significance of religious landmarks for urban identity in Antioch was investigated. The selected nine religious buildings were examined analyzed and evaluated by various techniques. As a result, in determination of Antioch city identity, religious buildings as strong landmarks were found effective. In this process their historical, cultural, symbolic, touristic values and being recognizable as religious buildings have great importance. Another finding is that location, shape and size which are related about phyisical difference are effective, but also inadequate for recognition. The study shows that protecting religious buildings which are identity elements of these settlement was not only sufficient, but it emphasizes that being perceivable is also important for these buildings. For this reason, religious buildings must be protected together with their surrounding structures at the siluette, purified from the additions for perceptions at urban scale and also provided sustainability of Antioch identity.
Keywords: Antioch; landmark; religious building; identity; PLACE ATTACHMENT; Public Administration